Learning by Doing再訪 : 表象変化に対する言語化の効果 - 新木, 眞司; 落合, 弘之; 三宅, なほみ (Cognitive Studies: Bulletin of the Japanese Cognitive Science Society, 1998)
This study shows some effects of verbalization on acquiring an abstract and flexible representation of how to solve a simple, well-formed puzzle. Subjects were either required to think-aloud or to keep silent while solving the five-disk Tower of Hanoi problem four consecutive times. On a transfer task of the eight-disk Tower of Hanoi problem, the subjects who had verbalized during the five-disk trials showed a stronger tendency to flexibly apply their abstracted understanding of the recursive structure of the problem. It was observed that during the verbalization the subjects commented rather freely on illegal moves like wanting to move the biggest disk under several other disks to the goal peg, or to move several disks as a pyramid to a different peg, both of which could have played important roles for helping the subjects acquire the abstract recursive structure. Some details are given for how concrete strategies emerged during the four verbalization trials, possibly leading to the observed representational change.